Evaluation of Legal Metrology Policy Implementation in Citeko Traditional Market: A Case Study - Junaedi, Edi; Muhtar, Entang Adhy; Buchari, Achmad (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
This study examines the effectiveness of Legal Metrology policy implementation in traditional markets, using Citeko Market in Purwakarta Regency, Indonesia, as a case study. It addresses issues of inaccurate weighing practices that disadvantage consumers and erode market trust. Employing a qualitative descriptive method, data was collected through interviews, field observations, and document analysis. Analysis was conducted using Winter’s (1990) policy implementation model, covering five dimensions: policy content, organizational coordination, management mechanisms, bureaucratic behaviour, and target group responses. The findings reveal weak inter-agency collaboration, inadequate daily oversight, and technical vulnerabilities in digital weighing instruments. Despite the existence of formal regulations and routine inspections, persistent gaps hinder consistent enforcement and consumer protection. The study concludes that implementation is only partially effective and recommends strengthening institutional coordination, increasing supervisory capacity, and enhancing public awareness to ensure fair trade and rebuild consumer trust.